Education in a mobile modernity. (21st November 2016) - Forsey, Martin
Abstract: The main contention of this paper is that education helps frame a modernity in which individual progress and achievement are increasingly linked to the sheer physical act of movement. Thinking of modernisation as a trajectory of progress and development symbolised by industrialisation and a reordering of 'traditional societies' through rational forms of governance, we can begin to recognise the importance of the disembedding of people and communities from local institutions and relations that these modernising processes continue to require. Individual education stories are filled with movement that often reflect a commitment to the mobility imperatives of modernity. Reflecting the different scales of practice evident in this mobile modernity, the empirical focus ranges from rural settings to urban mobilities and then out to transnational mobilities and the educational choices exercised by the global middle classes. The paper explores the profound and the mundane ways in which educational structures affect family and individual mobilities.